Fabrication of Schottky-Barrier Diodes Using a Thick Film Technique. (1984) - Sarin, R.; Pradeep, Y. R.
Abstract : Schottky-barrier diodes have been fabricated using a thick-film technique. A change in V–I characteristic with firing temperature has been observed. This technique is compatible with hybrid circuit technology.